FORAGING BEHAVIOUR OF FIVE EGRET SPECIES IN POME POND AREA AT CAREY ISLAND, PENINSULAR MALAYSIA - A. B. H. Aboushiba; R. Ramli; M. S. Azirun (Journal of Animal and Plant Sciences, 2013)
The foraging behaviour of five egret species in four POME ponds at Carey Island, Peninsular Malaysia was observed using 10 x 42 binoculars and digital video camera. The highest probing activity was recorded during 0900 to 1000hrs in Little Egret (Egretta garzetta; i.e. 52 probes/minute) followed by Cattle Egret (Bubulcus cormorandus; i.e. 42 probes/minute), Intermediate Egret (Mesophoyx intermedia; i.e. 20 probes/minute), Chinese Egret (Egretta eulophotes; i.e. 19 probes/minute) and Great Egret (Casmerodius albus; i.e. 5 probes/minute). In contrast, the lowest mean probing activity was recorded in Great Egret (0.4 probe/minute) as compared to Chinese Egret (1 probe/minute), Cattle Egret (2 probes/minute), Intermediate Egret (3 probes/minute), and Little Egret (4 probes/minute) during 1700 to 1800hrs. One- way ANOVA and Tukey’s (HSD) test indicated that the mean probing per minute of Little Egret, Intermediate Egret and Great Egret was significantly different (F4, 35 = 8.22, P < 0.05). The most frequent feeding behaviour sighted was walking slowly for Great Egrets (52.6%), walking quickly for Little Egrets (38.2%), moved slowly for Intermediate Egrets (38.2%), and walking slowly for both Cattle and Chinese Egrets (48.0% and 46.6% respectively). Cattle Egret was the only species showed gleaning behaviour in preying hidden invertebrates under soft mud while Little Egret was the only species that employ foot shuffling technique. The study revealed that feeding strategies employed by five egret species vary in term of sites selection and prey capturing technique.
Keywords: Foraging behaviour; Egret; POME; Carey Island; Probing